Microplastic and Nanoplastic Pollution in Pregnant Women: Contribution to Preterm Birth and Health Policy Implications - Arga Setyo Adji; Alan Dharmasaputra; Florencia Audrey; Grace Eka Wijayanti; Luh Putu Diah Ayuning; Bambang Edi Suwito; Angela Puspita (Postgraduate, University of Mataram, 2025)
Microplastic and nanoplastic pollution has emerged as a major environmental and public health issue, particularly in developing countries such as Indonesia, where contamination levels are among the highest in the world. Recent findings from Ekspedisi Sungai Nusantara (2022) revealed microplastic concentrations of up to 636 particles per liter in East Java’s rivers, indicating widespread exposure through water, air, and food sources. Indonesia also ranks third globally in plastic pollution, contributing approximately 3.4 million tons annually. This study employs a literature review and policy analysis approach to assess the impact of microplastic exposure on maternal and fetal health, with an emphasis on preterm birth risk and the adequacy of current regulatory frameworks. Evidence from human and animal studies indicates that microplastics can translocate across the placental barrier, inducing oxidative stress, inflammation, and endocrine disruption that may impair fetal development and increase the risk of preterm birth. Despite the implementation of the Regulation of the Minister of Health of the Republic of Indonesia No. 2 of 2025 concerning reproductive health, the absence of explicit environmental pollutant protection clauses highlights a critical policy gap. Strengthening intersectoral collaboration among the Ministry of Environment, the Ministry of Health, and the Ministry of Marine Affairs and Fisheries is essential to establish national safety thresholds, implement continuous monitoring, and integrate reproductive health protections into environmental policies. This study underscores the urgent need for comprehensive microplastic management strategies and maternal health safeguards to mitigate the growing risks associated with microplastic and nanoplastic exposure in Indonesia.